Bognár Rezső szerves kémikus egyetemi tanár, akadémikus, tudománypolitikus (1913-1990) - Herczegh, Pál (Gerundium, 2016)
rezső bognár, Professor of organic cheMistry, MeMber of the hungarian acadeMy of arts and sciences, scientific adviser. Rezső Bognár was one of the most outstanding students of Géza Zemplén, the irst great educator of organic chemistry in Hungary. When the School of Sciences was established in 1949 at the University of Debrecen, Professor Bognár was appointed head of the Department of Organic Chemistry. As a result of this decision, he became the founding father of organic chemistry work in Debrecen. Hewas soon elected member of the Hungarian Academy of Arts and Sciences and he served for two terms as Rector of Lajos Kossuth University of Arts and Sciences. Professor Bognár was founding president of the Debrecen Academic Committee, which position he held until his death. It was as the result of his nationally recognized public activity that the headquarters in Debrecen of DAB (=the Debrecen Academic Committee) and the Chemistry Building on the Debrecen campus were erected. He also organized the Antibio tic Chemical Research Group of the Hungarian Academy. he researchers of the Bognár school have brought out over 400 scientiic publications and submitted a large number of patents pertaining to the themes of the chemistry of carbohydrates, antibiotics, alkaloids, and lavonoids.His activities in the Hungarian National Assembly and the Hungarian Academy of Arts and Sciences have greatly contributed to the numerous successes of our university.